Cultural practices and pediatric hepatitis transmission: A study of HBV and HCV prevalence in Rural Sindh, Pakistan. - Abdul Qayoom Rakhshani; Zulfiqar Ali Laghari (International Journal of Endorsing Health Science Research, 2025)
Background: Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) are significant public health concerns in rural Pakistan, where limited healthcare access, low vaccination rates, and insufficient awareness contribute to ongoing transmission. If untreated, these infections can lead to serious liver complications, including cirrhosis and hepatocellular carcinoma. This study aimed to determine the prevalence of HBV and HCV among children in rural District Sanghar, Sindh, Pakistan, and to identify associated risk factors. Methodology: A cross-sectional study was conducted in three Union Councils (Shehdadpur, Sinjhoro, and Sanghar Taluka) of District Sanghar. A total of 1,123 children aged 4 to 9 years were screened for HBV and HCV using immuno-chromatographic (ICT) rapid strip tests. Data on hepatitis B vaccination status, parental education, and participation in traditional mourning rituals were collected through structured interviews. Statistical analyses, including chi-square tests and logistic regression, were used to identify significant associations. Results: Of the 1,123 children screened, 76% (n=854) were male and 24% (n=269) were female. Overall, 15 children (1.3%) tested positive for hepatitis, with HBV accounting for 73% (n=11) and HCV for 27% (n=4). Higher infection rates were observed among male children. Participation in traditional mourning rituals involving shared sharp instruments was frequently reported among infected cases. Additionally, low hepatitis B vaccination coverage and parental illiteracy were identified as significant contributing factors to infection risk. Conclusion: The study highlights the ongoing transmission of HBV and HCV among unvaccinated children in rural Sanghar, driven by inadequate vaccination coverage, limited parental education, and high-risk cultural practices. Targeted public health interventions, including expanded immunization programs and culturally sensitive community education, are essential to reduce hepatitis transmission in these vulnerable populations.